Determinants of Agricultural Productivity in the United State of America during the Period 1970-2017 - Boufenneche, Wassila (جامعة عنابة, 2021)
تهدف هذه الدراسة إلى تبيان أهم محددات الإنتاجية الفلاحية في الولايات المتحدة الأمريكية، من خلال دراسة قياسية لبيانات سنوية باستخدام منهج الانحدار الذاتي لفترات الإبطاء الموزعة خلال الفترة 1970-2017، وقد توصلت الدراسة إلى وجود علاقة توازنية طويلة الأجل بين الإنتاجية الفلاحية ومحدداتها الداخلة في تكوين النموذج القياسي، والمتمثلة في تمويل البحث والتطوير الفلاحي، استخدام الأسمدة، والإنفاق الحكومي على البنية التحتية للنقل وديون القطاع الفلاحي، بالإضافة إلى تأثير هذه المحددات إيجابا على الإنتاجية الفلاحية باستثناء ديون القطاع الفلاحي. This study aims to identify the most important determinants of agricultural productivity in the United States through an econometric study of annual data using autoregressive distributed lag approach during the period 1970-2017. The study found a long-term equilibrium relationship between agricultural productivity and its determinants in the econometric model. This is represented by agricultural research and development funding, use of fertilizer, government spending on transportation infrastructure and farm sector debt, in addition to the effect of these determinants positively on agricultural productivity except for farm sector debt.
Keywords: الإنتاج الزراعي -- التنمية الزراعية -- الاقتصاد الأمريكي